Higher Charlson Comorbidity Index Scores Are Associated With Increased Hospital Length of Stay After Lower Extremity Orthopaedic Trauma. Issue 1 (January 2017) - Lakomkin, Nikita; Kothari, Parth; Dodd, Ashley C.; VanHouten, Jacob P.; Yarlagadda, Mahesh; Collinge, Cory A.; Obremskey, William T.; Sethi, Manish K.
Abstract : Objectives: The purpose of this study was to explore the relationship between preoperative Charlson Comorbidity Index (CCI) and postoperative length of stay (LOS) for lower extremity and hip/pelvis orthopaedic trauma patients. Design: Retrospective. Setting: Urban level 1 trauma center. Patients/Participants: A total of 1561 patients treated for isolated lower extremity and pelvis fractures between 2000 and 2012. Interventions: Surgical intervention for fractures Main Outcome Measurements: The main outcome metric was LOS. Negative binomial regression analysis was used to examine the association between CCI and LOS while controlling for significant confounders. Results: One thousand five hundred sixty-one patients met the inclusion criteria, 1302 (83.4%) of which had lower extremity injuries and 259 (16.6%) experienced hip/pelvis trauma. A total of 1001 (64.1%) patients presented with a CCI score of 1 and stayed an average of 7.9 days. Patients with a CCI of 3 experienced a mean LOS of 1.2 days longer than patients presenting with a CCI of 1, whereas patients presenting with a CCI score of 5 stayed an average of 4.6 days longer. After controlling for age, race, American Society of Anesthesiologists score, sex, anesthesia type, and anesthesia time, a higher preoperative CCI was found to be associated with longer LOS for patients with lower extremity fractures (Incidence Rate Ratio: 1.04, P = 0.01). No significant association was found between CCI and LOS for patients with hip/pelvic fractures. Conclusions: This study demonstrated the potential utility of the CCI as a predictor of hospital LOS for lower extremity patients; however, the association may be small given the smaller Incidence Rate Ratio value. Further studies are needed to clarify the predictive value of the CCI for different types of orthopaedic injuries. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete.